Regional activity alterations in Parkinson’s disease patients with anxiety disorders: A resting-state functional magnetic resonance imaging study - Zhang, Peiyao; Zhang, Yanling; Luo, Yuan; Wang, Lu; Wang, Kang (Frontiers in Aging Neuroscience, 2022)
Background Previous studies have revealed alteration of functional connectivity (FC) in Parkinson’s disease patients with anxiety (PD-A), but local brain activities associated with anxiety in Parkinson’s disease (PD) patients remain to be elucidated. Regional homogeneity (ReHo) analysis was employed to investigate alterations of regional brain activities in PD-A patients. Methods Resting-state functional magnetic resonance imaging (rs-fMRI) data were acquired from 42 PD-A patients, 41 PD patients without anxiety (PD-NA), and 40 age-and gender-matched healthy control (HC) subjects. ReHo analysis was used to investigate the synchronization of neuronal activities in brain regions in the three groups. The relationship between ReHo value and anxiety score in the PD-A group was also investigated. Results Parkinson’s disease patients with anxiety showed increased ReHo values in the bilateral frontal lobes, caudate nucleus, and anterior cingulate gyrus [Gaussian random field (GRF) correction, voxel size p < 0.01, cluster size p < 0.05], compared with PD-NA patients and HC subjects, but the ReHo values of the right cerebellar hemisphere and posterior cerebellar lobe decreased (GRF correction, voxel size p < 0.01, cluster size p < 0.05). The increased ReHo values of the right superior frontal gyrus (r = 0.633, p = 0.001) and anterior cingulate gyrus (r = 0.45, p = 0.01) were positively correlated with anxiety scores in PD-A patients. Conclusion The development of PD-A may be associated with dysfunctional local activities in multiple brain regions, including the frontal cortex, cerebella, basal ganglia, and limbic system. Abnormal ReHo values in these brain regions may serve as neuroimaging markers for the early diagnosis of PD-A. The results suggest that using ReHo analysis to identify functional changes in core regions may advance our understanding of the pathophysiological mechanisms underlying PD-A.